SPESIFIKASI KUALITAS DALAM PENELITIAN KUALITATIF : TANGGAPAN ATAS ARTIKEL "ALIH KODE DALAM PROSES BELAJAR MENGAJAR EKSPRESI LISAN" - PUJIATI SUYATA (Jurnal Kependidikan, 2002)
Abstract Quantitative and Qualitative research have completely different paradigm. This paradigm implies to the difference in the research methodology and quality indicator. Quality indicators from a certain research could be seen from its validity and reliability. Quantitative research standard quality lies in its research instrument and its measurement. For that reason the instrument should have been measure on its validity and reliability. On the other hand, since a qualitative research  has different paradigm, the specification of validity and reliability are not the same. The standard specifications are: (1) credibility (2) transferability (3) dependability (4) conformability .The quality of qualitative research should be seen from that standard. Keywords: qualitative research, measurement validity